Penerapan Metode ARAS Dalam Menentukan Kelayakan Penerima Bantuan PKH Kelurahan Sudirejo-I Medan - Adinda Rahmadhani; Mesran; Alwin Fau (Forum Kerjasama Pendidikan Tinggi (FKPT), 2023)
Sudirejo-I Village, Medan City within a certain period of time determines the recipients of the Family Hope Program (PKH) assistance to its citizens. Providing cash assistance to the poor who require them to follow the requirements set by the Family Hope Program, namely sending their children to an education, and carrying out regular visits to health facilities for children aged 0 to 6 years, pregnant women and postpartum mothers. However, the provision of PKH social assistance at the Medan City Social Service is still not optimal. Because at the time of selecting the recipients of PKH assistance, there was no supporting system so that at the time of the selection process it was still using estimates and there was no calculation at the time of selecting the recipients of the assistance. So many residents protested because they should be more deserving of PKH assistance. The results of this study aim to create a Decision Support System in the provision of PKH social assistance using the ARAS method, which is one method that supports in helping to determine the eligibility of beneficiaries of the Family Hope Program (PKH), therefore a Decision Support System is needed. With this Decision Support System, it is expected to be able to minimize the occurrence of wrong targets that often arise in the selection process, the results of this study get the highest score obtained by A11 with a total value of 0.8648.